Analisis Data Kejadian Berulang Tidak Identik Dengan Cox Gap TimeModel - Andi Widya Rhezky Awalul Aziz; Yuki Novia Nasution; Sri Wahyuningsih (Program Studi Statistika FMIPA Universitas Mulawarman, 2017)
The gap time method is a method that can be used in recurrent event Time-based modelling. Gap analysis is often useful when events are relatively uncommon, when the object of the study is the prediction of time for the next event, or on the phenomenon of circulation.The analysis of model for non-identical recurrent events using survival time in the form of gap time is called Cox Gap Time Model. The purpose of this research is to know Cox Gap Time model for recurrent occurrence in DM type II disease and to know the factors that influence repetitive incident in DM type II disease in RSUD A. W. Sjahranie Samarinda. The variables in this research are age, treatment, status and relapse time (gap time). The study was conducted by using 263 medical records data of DM type II patients admitted to the hospital during observation period in January 2015 until December 2016. The results shows that age factor affects the first gap time and there are age, gap 1 covariate and gap 2 covariate that have significant effect aga inst to the third gap time variable, meanwhile there is no variable affects the second gap time.